Miliusa flaviviridis (Annonaceae), a new species from the southern Western Ghats, India - Page, Navendu V.; Poti, Meenakshi; Ravikumar, Kaliamoorthy (Phytotaxa, 2016)
Miliusa Leschenault ex A.DeCandolle (1832: 213) is characterized by a combination of floral characters such as sepaloid outer petals, densely hairy torus (receptacle), stamens with connectives not extending over the thecae and four-part lamellate ruminations of the endosperm (Chaowasku et al. 2013). Miliusa consists of ca. 50 species with four varieties, distributed from India, Sri Lanka and Bhutan to Australia through the Malayan islands, Philippines and Papua New Guinea (Mols & Keßler 2003). Chaowasku et al. (2013) included 27 species in their phylogenetic study and identified four well-supported clades, each characterized by a set of morphological characters. However, none of the species endemic to India was included in their study.